Anti-endothelial cell antibodies in idiopathic and systemic sclerosis associated pulmonary arterial hypertension - Tamby, M (BMJ Group, 2005)
Background: It has previously been shown that IgG antibodies from patients with limited cutaneous systemic sclerosis (SSc) bind to specific microvascular endothelial cell antigens. Since patients with limited cutaneous SSc are prone to develop pulmonary arterial hypertension (PAH), and since endothelial cell activation is involved in the pathogenesis of idiopathic PAH (IPAH), a study was undertaken to examine the presence of anti-endothelial cell antibodies in patients with idiopathic or SSc associated PAH. Methods: PAH was confirmed by right heart catheterisation (mean pulmonary artery pressure at rest >25 mm Hg). Serum IgG and IgM reactivities were analysed by immunoblotting on human macrovascular and microvascular lung and dermal endothelial cells from patients with IPAH (n = 35), patients with PAH associated with SSc (n = 10), patients with diffuse (n = 10) or limited cutaneous (n = 10) SSc without PAH, and 65 age and sex matched healthy individuals. Results: IgG antibodies from patients with IPAH bound to a 36 kDa band in macrovascular endothelial cell extracts with a higher intensity than IgG from other patient groups and controls. IgG antibodies from patients with IPAH bound more strongly to a 58 kDa band in microvascular dermal endothelial cells and to a 53 kDa band in microvascular lung endothelial cells than IgG antibodies from other patients and controls. IgG antibodies from patients with limited cutaneous SSc with or without PAH, but not from other groups or from healthy controls, bound to two major bands (75 kDa and 85 kDa) in microvascular endothelial cells. Conclusion: IgG antibodies from patients with idiopathic or SSc associated PAH express distinct reactivity profiles with macrovascular and microvascular endothelial cell antigens.